Pengembangan Aplikasi Pembelajaran Interaktif Mata Pelajaran IPA Di SD Negeri Pasirsari 01 - Afiyah, Neni Nur; Sasongko, Ananto Tri; Rahardjo, Sugeng Budi (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
SD Negeri Pasirsari 01 is a school located in South Cikarang District, Bekasi Regency. The learning media used by teachers in teaching science subjects (human respiratory system) still use textbooks and student worksheets (LKS) as guidelines because it is still difficult to develop new media that is more interactive. The results of the questionnaire using the Likert scale showed that 91.42% of students tended to be less interested in the science learning model. With this, it is necessary to design an android-based human respiratory system learning media. The method used is Research & Development with the Multimedia Development Life Cycle (MDLC) model. After being implemented and then tested using a questionnaire student response to the application with the results of the questionnaire using a Likert scale showing 37.14% of students tended to be less interested in the science learning model, it can be concluded that 54.28% of students liked science lessons.